Video Super-microsurgery Amplified using Close-up Lens Filter on the Operative Field Camera: Preliminary Report. Issue 8 (August 2018) - Kato, Motoi; Watanabe, Shoji; Watanabe, Azusa; Utsunomiya, Hiroki; Yokoyama, Takayuki; Watanabe, Taro
Abstract : Background: Super-microsurgery has widely spread due to the improvement of high magnification microscopes. The cost of multiple microscopes is high. Furthermore, the microscope heads are too large to fit in multiple surgical fields for pediatric patients. We adapted a 2-dimensional magnification system for performing lymphatic venous anastomosis on pediatric lymphedema cases. Methods: We attached a close-up lens filter to the suspended camera (CHZ-1, 360-PTR camera, Carina system, Tokyo, Japan) in the operative field. This was done to achieve 26× magnification using a small camera head, making it possible to perform super-micro anastomoses. Anastomoses time, scar length, and lymph vessel diameters were measured, and the outcomes were statistically analyzed and compared with the contralateral side. Results: Four pediatric lymphedema patients underwent the aforementioned technique, using the multisite microscopic approach. All anastomoses were completed within 20 minutes. The results were not significantly different from the conventional microscopic lymphatic venous anastomosis. Conclusion: This system is advantageous because (1) it has less costly initial investments; (2) it requires a small camera head, which provides available space for the multisite microscopic approach even for pediatric patients; and (3) it allows for a wider surgical working space.